Report of Meeting. The Sixteenth Debrecen-Katowice Winter Seminar Hernádvécse (Hungary), January 27–30, 2016 - AMSil, Redakcja (Annales Mathematicae Silesianae, 2016)
Report of Meeting. The Sixteenth Debrecen-Katowice Winter Seminar Hernádvécse (Hungary), January 27–30, 2016.